Analysis of Potential and Feasibility of Guest House Business in Rammang-Rammang Tourist Destination - Abdu Rahman; Andi Abriani; Andi Fatmawati (Journal La Bisecoman, 2024)
The rapid growth of the tourism and business sector in Maros Regency, especially with the popularity of Rammang-Rammang Tourism Attraction, has generated significant demand for accommodation. In response to this need, a study was conducted to evaluate the business potential of guest houses in the area. The research involves market surveys, marketing, and financial analysis. The results show that the guest house business has bright prospects, supported by high demand and positive financial analysis. Therefore, the guest house business in the Rammang-Rammang Tourism Attraction Area of Maros Regency is considered feasible to run. This study is expected to be a guide for potential entrepreneurs or investors who are interested in investing in the accommodation sector in the region.